2019
DOI: 10.1002/chem.201902784
|View full text |Cite
|
Sign up to set email alerts
|

A Germylene Supported by Two 2‐Pyrrolylphosphane Groups as Precursor to PGeP Pincer Square‐Planar Group 10 Metal(II) and T‐Shaped Gold(I) Complexes

Abstract: An efficient synthesis of 2-di-tert-butylphosphanylmethylpyrrole( HpyrmPtBu 2 ), by treating 2-dimethylaminomethylpyrrole( HpyrmNMe 2 )w ith tBu 2 PH at 135 8Ci nt he absence of any solvent,h as allowed the preparation of the new PGeP germyleneG e(pyrmPtBu 2 ) 2 (1), by treating [GeCl 2 (dioxane)] with LipyrmPtBu 2 ,i nw hich the Ge atom is stabilized by intramolecular interactions with one (solid state) or both (solution) of its phosphane groups.R eactions of germylene 1 with Group 10 metald ichlorido complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 108 publications
2
29
0
Order By: Relevance
“…However, germylene XXIX reacted readily with [AuCl(tht)] in THF at room temperature to give [Au{κ 3 P , Ge , P ‐GeCl(pyrmP t Bu 2 ) 2 }] ( 38 ; Figure ). Its XRD structure confirmed that the molecule arises from the insertion of the Ge atom of XXIX into the Au–Cl bond of the gold precursor, resulting in a complex containing a PGeP pincer chloridogermyl ligand attached in an uncommon T‐shape mode to the gold atom . DFT and QTAIM calculations indicated that the bonding between the Ge and Au atoms is a weak Ge→Au donor–acceptor interaction, a feature that contrasts with that found for T‐shaped PSbP pincer gold(I) complexes, in which the Au–Sb bonding is also weak but corresponds to an Au→Sb donor‐acceptor interaction (where the gold is the donor atom) …”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 92%
See 4 more Smart Citations
“…However, germylene XXIX reacted readily with [AuCl(tht)] in THF at room temperature to give [Au{κ 3 P , Ge , P ‐GeCl(pyrmP t Bu 2 ) 2 }] ( 38 ; Figure ). Its XRD structure confirmed that the molecule arises from the insertion of the Ge atom of XXIX into the Au–Cl bond of the gold precursor, resulting in a complex containing a PGeP pincer chloridogermyl ligand attached in an uncommon T‐shape mode to the gold atom . DFT and QTAIM calculations indicated that the bonding between the Ge and Au atoms is a weak Ge→Au donor–acceptor interaction, a feature that contrasts with that found for T‐shaped PSbP pincer gold(I) complexes, in which the Au–Sb bonding is also weak but corresponds to an Au→Sb donor‐acceptor interaction (where the gold is the donor atom) …”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 92%
“…An efficient synthesis of 2‐ditertbutylphosphanylmethylpyrrole (HpyrmP t Bu 2 ), by reacting 2‐dimethylaminomethylpyrrole (HpyrmNMe 2 ) with t Bu 2 PH at 135 °C in the absence of any solvent, allowed the preparation of the PGeP germylene Ge(pyrmP t Bu 2 ) 2 ( XXIX ) by treating GeCl 2 (diox) with two equivalents of LipyrmP t Bu 2 (Figure ). The Ge atom of XXIX is stabilized by intramolecular interactions with one (solid state) or both (solution) of its phosphane groups . In the solid state, the two pyrrolyl rings of germylene XXIX are almost perpendicular to each other and the ligand environment of the Ge atom is trigonal pyramidal (tetrahedral if it is considered that one vertex is occupied by the Ge lone pair), in contrast with the coplanar (or almost coplanar) disposition of the GeP 2 N 2 atom groupings of germylenes XXV and XXVII (see above).…”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 99%
See 3 more Smart Citations